2017
DOI: 10.1016/j.cub.2017.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Consistency of Spatial Representations in Rat Entorhinal Cortex Predicts Performance in a Reorientation Task

Abstract: Goal-directed behavior can be affected by environmental geometry. A classic example is the rectangular arena reorientation task, where subjects commonly confuse opposite but geometrically identical corners [1]. Until recently, little was known about how environmental geometry shapes spatial representations in a neurobehavioral context [2] (although see [3]). In the present study, we asked: Under what circumstances does the internal cognitive map predict behavior? And when does it fail to do so? To this end, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 45 publications
2
37
0
Order By: Relevance
“…However, we also occasionally observed global remapping between sessions (Figure 2J). Consistent with previous studies [14,15], coherent maps frequently ignored visual cues for alignment between sessions (Figure 3). Analyses done assuming adherence of spatial maps to arena cues revealed relatively low correlations (Figure S5B).…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…However, we also occasionally observed global remapping between sessions (Figure 2J). Consistent with previous studies [14,15], coherent maps frequently ignored visual cues for alignment between sessions (Figure 3). Analyses done assuming adherence of spatial maps to arena cues revealed relatively low correlations (Figure S5B).…”
Section: Resultssupporting
confidence: 90%
“…While some comparisons produced results consistent with these predictions, in most cases we found that mice utilized a coherent map: a configuration of place fields that maintain the same angle and distance from one another. Consistent with recent studies [14,15], however, we found that coherent maps frequently rotated in a manner that does not utilize specific arena cues or larger room cues for orientation. Maps were flexible as mice frequently employed a coherent map between the two different arenas while simultaneously modulating activity in a subset of cells to discriminate between them.…”
Section: Introductionsupporting
confidence: 91%
See 3 more Smart Citations